2014
DOI: 10.1136/bmjopen-2014-005066
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and severity of patient harm in a sample of UK-hospitalised children detected by the Paediatric Trigger Tool

Abstract: The measurement and examination of adverse events (AEs) that occur in children during hospital admissions is essential if we are to prevent, reduce or ameliorate the harm experienced. The UK Paediatric Trigger Tool (UKPTT) is a method of retrospective case note review that measures harm in hospitalised children.ObjectivesTo examine the harm resulting from the processes of healthcare in hospitalised children from centres providing data to the National Health Service (NHS) Institute UKPTT data portal, to underst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
40
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(43 citation statements)
references
References 29 publications
0
40
3
Order By: Relevance
“…The data in NADRMS showed that, in Sichuan Provincial People's Hospital, only 2 cases of pediatric ADR/ADE were reported from January 1 to September 30, 2017. The rate of positive triggers, PPV and ADE detection rate in our research, were higher than many previous studies which used trigger tools to detect pediatric ADE [7][8][9][10][11][12][13][14][15][16][17]36].…”
Section: Discussioncontrasting
confidence: 63%
See 1 more Smart Citation
“…The data in NADRMS showed that, in Sichuan Provincial People's Hospital, only 2 cases of pediatric ADR/ADE were reported from January 1 to September 30, 2017. The rate of positive triggers, PPV and ADE detection rate in our research, were higher than many previous studies which used trigger tools to detect pediatric ADE [7][8][9][10][11][12][13][14][15][16][17]36].…”
Section: Discussioncontrasting
confidence: 63%
“…45 literatures were retrieved through the literature search process, and 11 of them were in accordance with the inclusive criteria[7][8][9][10][11][12][13][14][15][16][17] . The quality level of one literature was grade B (score 5.5)[17] , and the other 10 were grade A (score 6 to 7)[7][8][9][10][11][12][13][14][15][16] . The included literatures which detected ADEs in pediatric inpatients by trigger tools were from Canada, Britain, United States, Australia, Sweden, Netherlands and China.…”
mentioning
confidence: 99%
“…Some have been adapted to specific paediatric settings and patient groups while others have focused on general (global) care. Trigger tools are designed and weighted towards the identification of common causes of harm, but they may also pick up other causes when broad definitions of harm are used [6]. What is emerging from the application of trigger tools is how frequently harm occurs in the paediatric inpatient hospital setting.…”
Section: Local Data On Harmmentioning
confidence: 99%
“…Measuring harm locally is important so that improvement efforts to reduce it can be guided and verified; however, these data can also be pooled to create a big picture view [6]. Other sources of big data include collaborative improvement networks that use multisite data to drive state-wide safety initiatives [12•].…”
Section: System-wide Data On Harmmentioning
confidence: 99%
“…Pediatric trigger tools have been found to be more effective than traditional incident management systems [3••, 4,33,34]. In the UK, the UK Pediatric Trigger Tool (UKPTT) has been developed as a way to measure harm in admitted pediatric patients [35]. The study, although retrospective, showed that there is a significant and measurable level of harm occurring to pediatric patients in the UK.…”
Section: Care At the System-wide Levelmentioning
confidence: 99%